Successful Retrieval of a 4-Year-Old Micra Transcatheter Pacemaker System in a Patient With Leadless Biventricular Pacing Therapy - Minami, Kentaro; Shtëmbari, Jürgen; Petrů, Jan; Chovanec, Milan; Funasako, Moritoshi; Hála, Pavel; Janotka, Marek; Škoda, Jan; Šedivá, Lucie; Reddy, Vivek Y; Neužil, Petr (JACC. Case reports, 2020)
This is the first report of the management of a patient with cardiac resynchronization therapy using leadless biventricular pacing. Successful retrieval of a 4-year-old Micra transcatheter pacing system (TPS) and reimplantation of a new Micra TPS prevented device-to-device interactions from multiple pacing devices in the right ventricle. (Level of Difficulty: Advanced.).